Eficacia de la aplicación de ejercicios propioceptivos guiados con puntero láser como estímulo óculo-motor en la respuesta biomecánica de la marcha en pacientes con Enfermedad Cerebro Vascular (ECV) que asisten al hospital Teodoro Maldonado Carbo (IEES) en el área de Terapia Física en el periodo de octubre del 2018 a febrero del 2019. - De la Cruz Muñoz, Ximena Estefanía (2019)
Introduction: Brain Vascular Disease (CVD) is the product of interruption of cerebral blood flow and presents with clinical signs of rapid evolution. The clinical feature of this disease is hemiplegia that causes an impairment in the biomechanics of walking due to the alteration of normal movement patterns. The guided proprioceptive exercises with laser pointer, the manipulation of these alterations through the application of the exercises to improve the balance, the amplitude of the base of sustentation, the step height and the step length, the use of oculomotor, proprioceptive and of coordination. Objective: The objective of this research was to determine the efficacy of guided proprioceptive exercises as an oculo-motor stimulus in the biomechanical response of gait in patients with stroke. Methodology: The research developed was experimental itself that aims to establish the possible effect of a cause that is manipulated. The investigative process is deductive because there is a problem that will be evaluated and tested in a sequential manner with an objective reality. The design of the study is experimental, because it modifies a reality by intentionally manipulating variables. It is pre-experimental because it is a design of a single group where the degree of control is minimal, by evaluating the population group at the beginning and at the end to collect data and demonstrate results. Outcomes: The guided proprioceptive exercises with laser pointer as an oculo-motor stimulus in the biomechanical response of the proposed gait should be considered for these alterations. In the results, improvements could be evidenced with a final percentage of equilibrium of 67% (Tinetti Scale); 57% in breadth of support base; 63% in step height and 60% in step length over 0% at the start of evaluations (Kinovea). Conclusion: The proprioceptive exercises guided with laser pointer as an oculomotor stimulation improved the biomechanical response of the gait.